Performance on Interdisciplinary Topics in an Integrated Pharmacy Course - Joie Rowles; Charles Veltri (University of Minnesota Libraries Publishing, 2017)
Objectives: Many colleges and schools of Pharmacy combine interdisciplinary topics such as pathophysiology, pharmacology, medicinal chemistry and therapeutics into one integrated course. Our main aim for this study is to determine if students pass integrated courses and yet fail to pass interdisciplinary sections of those courses. Methods: Two representative integrated sequence courses were evaluated without any study-imposed intervention. Individual student examination scores (~140 students) were evaluated for overall performance as well as for performance on the interdisciplinary topics of pathophysiology/pharmacology, medicinal chemistry, and therapeutics. The degree of difficulty of the examination questions, as well as the test item discrimination, were also measured. Results: There were students that passed the course but failed one, or more, of the interdisciplinary topics. Combining data from both courses, medicinal chemistry was the most frequently failed discipline (29 students), followed closely by pharmacology (22 students), and distantly by therapeutics (1 student). The examination questions for medicinal chemistry were not more difficult nor more discriminatory than the questions for the other disciplines. Conclusions: These data indicate that students pass integrated courses, but fail to pass interdisciplinary sections of those courses, especially the pharmaceutical sciences. It is not known if these results are consistent, nor what long-term adverse consequences may result. These results inform curricular and assessment aspects of the pharmacy academy as pertains to establishing the scientific foundation required by the CAPE 2013 Educational Outcomes.   Type: Original Research